Arterial Vascularization of the Forehead in Aesthetic Dermatology Procedures: A Review - Kliniec, Katarzyna; Domagała, Zygmunt; Kempisty, Bartosz; Szepietowski, Jacek C (Journal of clinical medicine, 2024)
Background: The growing popularity of aesthetic procedures on the face raises the question of their safety. The forehead region is crucial aesthetically, but due to its abundant vascularization, it is also one of the most dangerous areas for dermatologic procedures, especially in the glabella area. The purpose of this article is to review the literature on the arterial vascularization of the forehead to identify potential high-risk zones for aesthetic dermatology procedures. Methods: A database search (PubMed, Web of Science, Scopus, and Embase) was conducted, and the titles and abstracts of all identified studies were screened, followed by full-text evaluation. Results: We identified 714 articles during the database search, and 25 articles were included in the review. The included studies used cadaveric dissection and computed tomography applied to cadavers as well as Doppler ultrasonography on volunteers to evaluate the forehead arteries (supratrochlear (STrA), supraorbital (SOA), central (CA), paracentral artery (PCA), and frontal branch of superficial temporal artery(FBSTA)). A total of 1714 cases involving the forehead arteries were analyzed. The included arteries were observed over a relatively large area, and their locations varied. The CA and PCA in cadaver studies were observed in an area of 0.2 to 10.8 mm and 0.8 to 16.2 mm, respectively, on the entire path from the glabellar point to the frontal prominence point. The distances from the midline in cadaveric studies at various measurement points ranged from 0.6 to 28.0 mm for the superficial branch of the STrA and 13.6 to 40.7 mm for the deep branch of STrA. In case of SOA, the distance from the midline ranged from 23 to 32 mm. Measurements from the midline in Doppler studies ranged from 0 to 23 mm for STrA and from 10 to 50 mm for the SOA. In studies using computed tomography, STrA was observed at a distance of 11 to 21 mm and the SOA at a distance of 21 to 32 mm, both lateral to the midline. Conclusions: Medical professionals should be aware of zones where frontal arteries are more likely to be encountered. The glabella region appears to be one of the most dangerous areas for dermatologic procedures. It is believed that the supratrochlear, supraorbital, and the paracentral arteries may cause ophthalmic complications due to occlusion of the ophthalmic artery, while this risk for the frontal branch of the superficial temporal artery seems to be low but cannot be completely excluded.